Assessment of the small‐capacity straight‐bladed VAWT for sustainable development of Canada - Islam, Mazharul; Ting, David S‐K.; Fartaj, Amir (Taylor & Francis, 2007)
Canada has a huge wind power potential of more than 28,000 MW, which represents a significant environmentally benign sustainable energy source. A small-capacity (below 10kW) straight-bladed vertical axis wind turbine can compete with conventional sources in niche markets. It converts wind energy to useful energy vectors or carriers, such as heat, electricity, and mechanical power. This paper discusses the applications of this turbine, so promising for the sustainable development of Canada. Furthermore, human health, natural environmental and national economic benefits of these applications in Canadian perspective are also described. It has been demonstrated that all these environmentally benign applications can contribute significantly toward Canada's target of reducing greenhouse gas emissions by displacing the use of conventional fossil fuels, and take an essential step toward sustainable energy future. © 2007 Taylor & Francis.